Juan de Dios Vial Correa : pasión por la universidad (EDICIONES UC, 2018)
The Pontifical Catholic University of Chile has become one of the most important in Latin America in recent decades. This is due to the work of many people, among others, that of whoever was its rector between 1985 and 2000: the doctor Juan de Dios Vial Correa. This book includes a selection of articles, speeches, interviews, and letters, both from his time as rector and from the years before and after his tenure. Through them, topics of the greatest relevance appear, such as university reform, the importance of Catholic universities for the country, the value of science and the training of young people, aspects of the teaching of the Catholic Church or the challenges of the university system. Chilean. In these areas Vial was a witness and actor of a crucial time and of great changes in Chile. This book allows us to know the university and social thought of the Vial rector, as well as takes us into the evolution of the Catholic University in the last decades of the 20th century. The work has a preliminary study by the historian Alejandro San Francisco, who also edited this work.